Peranan Kinerja Karyawan BAZNAS Kota Bogor dalam Meningkatkan Kepercayaan Muzakki - Setiovani, Nisha Azzahra; Rahman, Arif; Yuningsih, Yuyun (Tadbir: Jurnal Manajemen Dakwah, 2022)
Muzakki’s trust is an important factor in increasing the collection of zakat funds to be more optimal. This study aims to find out the efforts applied by BAZNAS Bogor City in order to increase muzakki trust, know employee work discipline, know the form of employee work motivation and know the evaluation that has been applied by BAZNAS Bogor City to the level of muzakki trust. The method used in this study is a qualitative descriptive method. Data collection techniques through observation, interviews, documentation, interviews, documentation. The results of this study are known that are efforts are: (The Anugerah Zakat Program, (2) Communicating directly or indirectly with muzakki, (3) Maintaning fund transparency through reporting the Radar Bogor Newspaper as well as websites and social media. Work discipline can be seen from employees who work according to standard operating procedures (SOPs) and permits if they do not come to work. Provision of motivation by superiors during monthly routine recitations. As well as evaluations every month, semester and yearly that discuss and find solutions to various obstacles are effective.